P408 CERTIFICATION FOR COMPETITIVE SPORTS ACTIVITY IN A TEENAGER WITH WPW BY VIA INTRAHYSSIAN ACCESSORY PATHWAY. (18th May 2022) - Stuto, A; Armaro, B; Cosentino, E; Canonico, G; Ambu, A; Cascone, G; Lo Giudice, A; Canonico, S; Cassarisi, S; Ierna, S; Basile, G; Gulletta, S
Abstract: The case of a 12–year–old male, height 160 cm, weight 46 kg, who practices water polo at a competitive level is reported. Negative family history of cardiovascular pathologies, general and cardiovascular physical examination within the limits of normality. On the electrocardiographic trace (ECG) presence of delta wave from ventricular pre–excitation from intrahyssian accessory pathway (Fig. 1 ). Echocardiography + color Doppler was normal. The subject underwent a cardiopulmonary stress test with an incremental ramp protocol and steps of 20 watts / min. Shutdown at 190 watts for muscle exhaustion with peak oxygen consumption (VO2) = 43.9 mL / Kg / min, Heart rate = 197 beats / minute, BP = 210/70 mmHg, VE / VCO2 slope = 27.6. Normal course of the cronotropic and pressure curve. The ventricular pre–excitation delta wave persisted for the entire duration of the test and in recovery (Fig. 2, Fig. 3 ). Secondary disturbances of ventricular repolarization characterized by ST segment sub–leveling and negative T wave appeared at high load and persisted in the first minutes of recovery, delta VO2 / delta WR = 12. Given the non–disappearance of the delta wave from ventricular pre–excitation during the maximal stress test, the subject was sent to an electrophysiological study and subsequent ablation of the accessory pathway. The electrophysiological study was negative for inducibility of atrial fibrillation (AF) and ventricular arrhythmias. Safe ablation was impossible given the intrahyssian position of the accessory pathway. Considering the negativity of the electrophysiological study due to non inducibility of supraventricular and ventricular arrhythmias, eligibility for competitive sports was granted.